Evaluating the Validity of an Epistemic Belief Questionnaire: Evidence Based on Internal Structure, Content, and Response Process - Anindito Aditomo (Faculty of Psychology, Universitas Surabaya, 2014)
The development of epistemic beliefs is regarded as an important goal of education. Three studies were conducted with preservice teachers in Australia to evaluate the validity of a new instrument that has the potential to measure sophistication of epistemic beliefs in a theoretically grounded manner. Two surveys gathered evidence on internal structure and content, and an interview study collected evidence on response process. Findings indicate that the original model and instrument required modifications. The modified instrument exhibited better internal structure. Interview data show that the instrument prompted respondents to think about the target constructs. However, the interview data also show that there are nuances in respondents’ beliefs about scientific knowledge which were not captured by the written questionnaire. Pengembangan keyakinan epistemologi (ilmu pengetahuan) pada siswa dianggap sebagai salah satu tujuan penting pendidikan. Artikel ini memaparkan hasil tiga studi pada guru- guru magang di Australia mengenai validitas sebuah instrumen baru yang mengukur perkembangan keyakinan epistemologi. Dua studi survei menyajikan bukti tentang konten dan struktur internal, dan sebuah studi wawancara memaparkan bukti mengenai proses merespons. Survei pertama menunjukkan bahwa model original dan instrumennya perlu dimodifikasi. Survei kedua menunjukkan bahwa instrumen hasil modifikasi memiliki struktur internal yang lebih baik. Data wawancara menunjukkan bahwa instrumen tersebut memaksa para responden untuk memikirkan konstruk yang disasar. Namun, data wawancara juga menunjukkan adanya nuansa dalam keyakinan responden tentang pengetahuan ilmiah yang tidak terungkap melalui kuesioner tertulis tersebut.